ANALISIS KINERJA KEUANGAN USAHA PENGGEMUKAN SAPI DAN KAMBING (STUDI KASUS DI CV. ABK, KABUPATEN LAMPUNG SELATAN - Dwi Lestari, Maya; Abbas Zakaria, Wan; Haryono, Dwi (Journal of Food System & Agribusiness, 2023)
The purpose of this study was to analyze the financial business performance of cattle and goats rearing in CV. ABK. This research is a case study located in Candi Mas Village, Natar District, South Lampung Regency, Lampung Province. The choice of location was done deliberately. The analytical method used is the analysis of financial performance which includes profitability ratios, liquidity ratios, and solvency ratios. Overall, the business of cattle and goats rearing in CV. ABK South Lampung Regency is a good category. The average value of the liquidity ratio, namely the current ratio (486.76%) and the quick ratio (310.68%) are more than a predetermined standard. The average value of the solvency ratio, namely the Debt to Asset Ratio (5.26%) and Debt to Equity Ratio (6.30%) is not more than 50%. The average value of the profitability ratio, namely Profit Margin (10.99%), Return on Equity (22.53%), and Return on Assets (21.54%) is more than 1.5%. Decrease in financial performance in 2020 profitability ratios was due to the impact of Covid-19. However, in 2021 the performance of the cattle and goat rearing business at CV. ABK began to improve.